2018
DOI: 10.1063/1.5009182
|View full text |Cite
|
Sign up to set email alerts
|

A simple, space constrained NIRIM type reactor for chemical vapour deposition of diamond

Abstract: In this paper the design of a simple, space constrained chemical vapour deposition reactor for diamond growth is detailed. Based on the design by NIRIM, the reactor is composed of a quartz discharge tube placed within a 2.45 GHz waveguide to create the conditions required for metastable growth of diamond. Utilising largely off-the-shelf components and a modular design, the reactor allows for easy modification, repair, and cleaning between growth runs.The elements of the reactor design are laid out with the CAD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to [ 45 ], diamond films prepared mainly by the CVD method consist of many small micro-/nano-crystalline diamonds surrounded by a graphitic or amorphous carbon phase mainly occurring at their grain boundaries. Due to the presence of these phases, C-H bonds and C-C and C=C transpolyacetal chains are bent/stretched, which causes the appearance of a Raman peak in the region of 1140 cm −1 [ 46 , 47 ] (see the NDs pattern in Figure 6 ). Additionally, the authors of [ 45 ] state that the graphitic (G) peak observed in NDs films prepared in this way was shifted from the graphitic peak of 1580 cm −1 downwards to a broad band in the region of 1500 to 1600 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to [ 45 ], diamond films prepared mainly by the CVD method consist of many small micro-/nano-crystalline diamonds surrounded by a graphitic or amorphous carbon phase mainly occurring at their grain boundaries. Due to the presence of these phases, C-H bonds and C-C and C=C transpolyacetal chains are bent/stretched, which causes the appearance of a Raman peak in the region of 1140 cm −1 [ 46 , 47 ] (see the NDs pattern in Figure 6 ). Additionally, the authors of [ 45 ] state that the graphitic (G) peak observed in NDs films prepared in this way was shifted from the graphitic peak of 1580 cm −1 downwards to a broad band in the region of 1500 to 1600 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…This peak corresponds to the vibrational mode involving the stretching and compression of the carbon-carbon (C-C) bonds in the DNPs lattice. Furthermore, the emergence of the G-band peak at approximately 1550 cm −1 can be observed, indicating the presence of in-plane stretching of sp2 bonds within the graphite-like substances [20]. The possible ball-stick and polyhedron structures of DNPs are shown in Figure 1c,d.…”
Section: Characterizationsmentioning
confidence: 92%
“…in Figure 3a) is attributed to first order Raman resonance peak, however, the Raman peak is much broader compared to the as-grown BDD (Curve I. in Figure 3a), which indicates the formation of nanocrystalline diamond particles. [38,39] In addition, a shoulder peak to the first-order Raman resonance peak has appeared at 1355 cm −1 (Figure 3a), which corresponds to the disordered carbon (Dband). [40] The existence of graphitic (sp 2 ) carbon phase by the annealing of Mn-BDD was evidenced by the broad Raman resonance peak centered at 1591 cm −1 of G-band (Figure 3a), demonstrating a shift from 1550 cm −1 (as-grown BDD) to 1591 cm −1 (annealed Mn-BDD).…”
Section: Characterization Of Mn Ion-implanted Boron Doped Diamond Filmsmentioning
confidence: 99%